Meteorology today - Ahrens, C. Donald
For instructors wanting all the detail of METEOROLOGY TODAY, but that don't have time to cover all of the chapters, the new "core version" includes only the first sixteen chapters of the text, eliminating the chapters on air pollution, global climate, and light and atmospheric optics. If there is a better organization to more perfectly suit your course, the text can be further customized using TextChoice, the Cengage Learning Custom Solutions. Contact your local Cengage Learning representative to learn more